Factors contributing to exercise tolerance in patients with coronary artery disease undergoing percutaneous coronary intervention - Husheng Li; Minqian Wei; Lili Zhang; Lan Huang; Yiyan Wang; Jiaqi Wang; Shaowei Zhuang; Xubo Wu; Jing Wu (BMC, 2023)
Abstract Background Exercise tolerance plays a vital role in the process of cardiac rehabilitation in patients undergoing percutaneous coronary intervention (PCI). The study sought to determine the characteristics, risks and correlates of post-PCI exercise tolerance in patients with coronary artery disease (CAD). Methods We analyzed clinical data of 299 CAD patients undergoing elective PCI and completing cardiopulmonary exercise testing (CPET). According to the Weber classification, post-PCI exercise tolerance was evaluated by peak oxygen uptake (VO2 peak). We assessed the impact of 34 predefined clinical features, cardiac functional parameters, and blood biochemistry data on exercise tolerance by univariate analysis and logistics regression analysis. Results Of 299 patients, 74.92% were men and average age was 60.90 ± 10.68 years. VO2 peak in the entire population was 17.54 ± 3.38 ml/kg/min, and 24.41% (n = 73) were less than 16 ml/kg/min, who were considered to have exercise intolerance. Multivariate logistics regression results showed that sex, diabetes mellitus, number of stents, left atrial diameter (LAD), end-diastolic volume (EDV), and hemoglobin influenced the peak oxygen uptake of CAD patients undergoing elective PCI. (All p < 0.05). Conclusions Nearly one quarter of CAD patients have exercise intolerance in the early post-PCI period. Female, diabetes mellitus, number of stents, LAD, EDV might negatively impacted post-PCI exercise tolerance, which need further warrant by large scale cohort study.